Análise da competência da escola através dos instrumentos por ela considerado avaliadores do processo pedagógico: testes e provas - Lima, Adriana Flavia Santos de Oliveira (1992)
This work's objectives may be summarized in the study of three different aspects of School Evaluation: 1) School competence on what concerns: a) Knowledge of the cognitive structure's development (Iearning theory) and b) inadequacy of contents with regard to this cognitive process these contents' uselessness and outdated characteristics. 2) End of school responsability over learning: reducing learning processes to evaluation systems ('pedagogy of examination'). 3) School evaluation as an instrument of power in the teacher-student relation (expanding itself in a network that involves and subordinates school, parents and socity as a whole). This work 's theoretic bases were the following: a) Jean Piaget - the Genetic psychology - in studying the cognitive development and the adequacy of school contents; b) Michel Foucault and Lauro de Oliveira Lima - in studying power relations. As synthesis to the conclusions arrived at we can enumerate: 1) Teachers and school are not acquainted with elements of the psychology of development and do not have a defined learning theory. 2) For its ecleticism and contradictions, school demonstates the nonexistance of an organized pedagogic proposition (goals, means and technologies ). 3) School contents are based on curricular traditions which are not updated (useless) and do not follow the process of development and the interest of children and youths. 4) Evaluation methods are predominantly (over 70%) quantitative and bureaucratic (grammar and calculation). Sut teachers do not command the technology of test elaboration, not even on what concerns the quantitative approach chosen by them. 5) School exempts itself from the responsibility of guaranteeing the acquisition of knowledge (Iearning) and becomes an information transmitter (which is outdated and sometimes useless). 6) Reduction of learning (pedagogic process) to evaluation transform it in the main and most strong instrument of power.